The Impact of Lavandula officinalis essential oil on growth performance and hematology of common carp (C.carpio) - mahmood, shaima; Sadraddin, Avan; Namiq, Karzan (Iraqi Journal of Aquaculture, 2024)
Eﬀects of lavender essential oil (LEO) on the growth, haematology and biology of common carp was investigated. A total of 108 healthy ﬁshes were distributed into 12 plastic tanks to four treatments in triplicate. The ﬁsh were fed a diet consisting of 0, 1 ml, 2 and 4 ml/kg of LEO for 60 days. Results showed that WG and SGR signiﬁcantly were increased at the diﬀerent levels of LEO (p < .05). The highest of WG was found in (T4) and 4 ml/kg of LEO and SGR was found in (T3) 2 ml/kg of LEO of LEO. In contrast, FCR was decreased with increasing of dietary supplemental of LEO there were significant differences (p <0.05), for (hgb, mch and wbc). However, there were no significant differences for (rbc, mchc, plt, mcv, granules, lymphocyte and monocyte) of LEON treatment compared to the control (p < .05). Finally, there were significant differences for biological traits except Hepatosomatic index and Spleenosomatic index. Overall, our results interestingly demonstrated that the eﬀect of supplemental dietary LEON had a positive and signiﬁcant eﬀect on some growth, hematological and biological traits of common carp.